Long-Term Prognostic Value of Stress Cardiovascular Magnetic Resonance–Related Coronary Revascularization to Predict Death: A Large Registry With >200 000 Patient-Years of Follow-Up. (October 2021) - Pezel, Théo; Unterseeh, Thierry; Garot, Philippe; Hovasse, Thomas; Sanguineti, Francesca; Toupin, Solenn; Morisset, Stéphane; Champagne, Stéphane; Garot, Jérôme
Abstract : Background: Although the benefit of coronary revascularization in patients with stable coronary disease is debated, data assessing the potential interest of stress cardiovascular magnetic resonance (CMR) to guide coronary revascularization are limited. We aimed to assess the long-term prognostic value of stress CMR-related coronary revascularization in consecutive patients from a large registry. Methods: Between 2008 and 2018, a retrospective cohort study with a median follow-up of 6.0 years (interquartile range, 5.0–8.0) included all consecutive patients referred for stress CMR. CMR-related coronary revascularization was defined by any coronary revascularization performed within 90 days after CMR. The primary outcome was all-cause death based on the National Death Registry. Results: Among the 31 762 consecutive patients (mean age 63.7±12.1 years and 65.7% males), 2679 (8.4%) died at 206 453 patient-years of follow-up. Inducible ischemia and late gadolinium enhancement by CMR were associated with death (both P <0.001). In multivariable Cox regression, inducible ischemia and late gadolinium enhancement were independent predictors of death (hazard ratio, 1.61 [99.5% CI, 1.41–1.84]; hazard ratio, 1.62 [99.5% CI, 1.41–1.86], respectively; P <0.001). In the overall population, CMR-related coronary revascularization was an independent predictor of greater survival (hazard ratio, 0.58 [99.5% CI, 0.46–0.74]; P <0.001). In 1680, 1:1 matched patients using a limited number of variables (840 revascularized, 840 nonrevascularized), CMR-related revascularization was associated with a lower incidence of death in patients with severe inducible ischemia (≥6 segments, P <0.001) but showed no benefit in patients with mild or moderate ischemia (<6 segments, P =0.109). Using multivariable analysis in the propensity-matched population, CMR-related revascularization remained an independent predictor of a lower incidence of all-cause mortality (hazard ratio, 0.66 [99.5% CI, 0.54–0.80], P <0.001). Conclusions: In this large observational series of consecutive patients, stress perfusion CMR had important incremental long-term prognostic value to predict death over traditional risk factors. CMR-related revascularization was associated with a lower incidence of death in patients with severe ischemia. Abstract : Supplemental Digital Content is available in the text.